2020
DOI: 10.1002/ps.5847
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of selected larvicides for the control of Culex pipiens biotype pipiens and Culex pipiens biotype molestus under laboratory and semi‐field conditions

Abstract: BACKGROUND: The insecticidal efficacy of selected mosquito larvicides [teflubenzuron, S-methoprene, diflubenzuron, temephos, Bacillus thuringiensis var. israelensis (Bti) and polydimethylsiloxane (PDMS)], applied alone or in combination, against two Culex pipiens biotypes, Cx. p. pipiens and Cx. p. molestus, was compared under laboratory and semi-field conditions. Registered larvicides were evaluated at the label dose, whereas those not registered for mosquito control were tested at the label dose per area, i.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 27 publications
(36 reference statements)
0
8
0
Order By: Relevance
“…The use of PDMS has been proposed in large areas, such as catchments, but also in the urban and suburban environment, where the use of other insecticides is not always possible. In a recent study, Rumbos and Athanassiou ( 2020 ) indicated that this formulation was effective for the control of the biotype tested here, but also for Cx. pipiens biotype molestus , even at concentrations that were lower than the label rate.…”
Section: Discussionmentioning
confidence: 67%
See 3 more Smart Citations
“…The use of PDMS has been proposed in large areas, such as catchments, but also in the urban and suburban environment, where the use of other insecticides is not always possible. In a recent study, Rumbos and Athanassiou ( 2020 ) indicated that this formulation was effective for the control of the biotype tested here, but also for Cx. pipiens biotype molestus , even at concentrations that were lower than the label rate.…”
Section: Discussionmentioning
confidence: 67%
“…pipiens biotype molestus , even at concentrations that were lower than the label rate. In that study, the authors found that PDMS had a remarkable “speed of kill,” as all larvae were dead after 3 days of exposure in semi-field tests, while larval mortality ranged between 60 and 88% even from the first day (Rumbos and Athanassiou 2020 ). Previous laboratory and field/semi-field tests confirmed the high efficacy of this insecticide for additional species of the genera Culex , Aedes , and Anopheles (Cilek et al 2020 , Webb and Russell 2009 , 2012 ).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…To reduce the present reliance on insecticide-based mosquito control, bio-control solutions aim to be long-term control agents and target a variety of mosquito species [ 12 ]. Bacillus thuringiensis ( Bti ) formulations [ 13 , 14 ], for example long-lasting Ae. albopictus larvicidal Bti -blocks, are highly effective in vector control strategies [ 15 ] and plant essential oils used for mosquito control [ 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%